Modeling competitive sorption of lead and copper ions onto alginate and greenly prepared algal-based beads. (May 2017) - Wang, Shengye; Vincent, Thierry; Faur, Catherine; Guibal, Eric
Graphical abstract: Pure algal beads ( Laminaria digitata ) shows marked preference for Pb(II) binding over Cu(II) – modeling of competitive sorption by the Sips equation. Highlights: Alginate, algal-based beads are efficient sorbents for Pb(II) and Cu(II). Pb(II) is preferentially sorbed compared to Cu(II). Algal beads are more selective than algal/PEI composite beads. The competitive Sips model gives the best fit of experimental sorption isotherms. Abstract: The binary sorption of Pb(II) and Cu(II) onto calcium alginate, algal biomass and algal/glutaraldehyde-crosslinked polyethyleneimine (PEI) composite beads was studied in the absence and presence of Ca(II). Different competitive models were compared for predicting the equilibrium data. Results show that all the sorbents have a significant preference for Pb(II) over Cu(II) in Pb-Cu system: the separation factors reach 14.1, 9.1 and 3.6 for alginate, algal biomass and algal/PEI beads, respectively. Kinetic studies confirm the occurrence of an ion-exchange mechanism between Pb(II) and Cu(II) as the sorption sites are progressively saturated. Competitive Sips model predicts well the sorption data for all the sorbents. In Pb-Cu-Ca system, the Cu(II) sorption by algal beads was negligible, while algal/PEI still maintained a significant sorption of Cu(II) sorption under these conditions.